Adsorption mechanisms of linear and branched alkane liquid on solid surfaces that influences heat transfer - Rafeq S, A.; Daud, N. M.; Sudin, M. N.; Zakaria, M. S.; Rosli, M. A. M.; Munir, M. F.; Manshoor, B. (2024)
The contact interfaces of solid and liquid are common systems in tribology studies where the main parameter looked at are the wear rates and scar. These problems of wear rates and scar are evaluated by adsorption mechanisms. The main contributors of these problems are the character of liquid orientation on solid surfaces that required deep analysis of molecular orientations. Thus, the main purpose of this study is to look at the adsorption mechanisms of liquid on solid surfaces based on the structural quantities of density and orientation order parameters. The simulation system of solid of gold with surfaces of face-centered cubic (FCC) of (100) in contact with three types of alkanes (pentane, heptane and 3- ethyl-pentane) is modeled using molecular dynamics simulations. A uniform temperature is applied throughout the simulation system at 0.7 of the critical temperature of the liquid. It is found that, the adsorption behavior of liquid with linear molecular length is higher as compared to liquid with branches in the molecular, this in away influences the heat transfer near the contact interfaces of solid and liquid. However further investigation is needed to observe the influence of surface structure of the solid surfaces